Emas Syariah di Pt Bank Syariah Indonesia KC Mekanisme Pembiayaan Gadai Padang Sidempuan - Pane, Jihan Atiqah; Tambunan, Khairina (Regress: Journal of Economics & Management, 2022)
Bank Syariah Indonesia KC Padangsidempuan was previously a Bank Mandiri Syariah which eventually merged to become a part of the Branch Office of Bank Syariah Indonesia. Where operational sharia banks and their products are developed on the basis of the Qur'an and Hadith, strengthened by laws, BI regulations and DSN-MUI Fatwas. In this study, we will discuss specifically one of the financing products that can be said to be of great interest to the local community, namely the Gold Pawn Financing. In writing the researchers used techniques such as data collection in the form of observation, literature study and interviews. Furthermore, the method in this research is a qualitative approach. The purpose of this paper, the researcher hopes that the reader can find out more clearly the flow of the Gold Pawn financing process at Bank Syariah Indonesia KC Padangsidempuan The conclusion in this study is about the Islamic Pawning Financing Mechanism at PT Bank Syariah Indonesia Padangsidempuan Branch Office where researchers will discuss the legal basis and pillars in Sharia Pawn financing, the mechanism for applying for Pawn Gold financing, the implementation of the handover of goods and collateral documents, and those related to Sharia Pawn settlement system before/after maturity.